If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4m+14-2m=0
We simplify the equation to the form, which is simple to understand
4m+14-2m=0
We move all terms containing m to the left and all other terms to the right.
+4m-2m=0-14
We simplify left and right side of the equation.
+2m=-14
We divide both sides of the equation by 2 to get m.
m=-7
| -3.5y=-50 | | 7x+24=2x-6 | | 4.5-2.6+x=9 | | -9b+13-12=10 | | 75n=30 | | -4(x-2)=-40 | | 25+4-6=12 | | 3x-40=6x-10 | | 46-12+6=12 | | 4+3-5=7 | | 3+4(X+4)=27 | | 9x^2+36x+14=0 | | R+(-1.5)=-3.4 | | 18u(8)w(8)+30u(6)w(5)y(4)= | | 11x-2=x | | -15+8-14=35 | | 4-3+5=7 | | 3(7x-7)+13x= | | 4500+(4*x)+600=10,500 | | 11-(3x-6)+2(2x+5)-x= | | 4x+14-6=7 | | 45+16-2=14 | | (3*1500)+(4*x)+(3*200)=10,500 | | 0.4m-3= -1 | | 3x-5(x-5)=-6+3+21 | | 6+12+3=39 | | 45-16+2=14 | | y=7x^2-4x-8 | | 3-18x+4=-88 | | 2-(9-a)=4a-10 | | .75*q=15 | | 14*4-6=12 |